STRATEGY FOR ENSURING FINANCIAL SECURITY OF TEXTILE ENTERPRISES (World Bulletin of Management and Law, 2024)
In this paper has been suggested ways to eliminate economic and financial risks in enterprises, substantiates ways to eliminate economic and financial risks in enterprises, mechanisms for optimal management of ensuring financial security in enterprises, and proposes a strategy for ensuring financial security in enterprises.